MEKANISME PENYELESAIAN TINDAK PIDANA ILEGAL FISHING DI INDONESIA - Maulana, Wahyu; Gultom, Elfrida Ratnawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This study examines the mechanism of resolving illegal fishing offenses in Indonesia using a normative juridical approach. The data utilized consist of literature and secondary data comprising primary and secondary legal materials related to the criminal offense. The research findings indicate that the procedures for handling illegal fishing offenses are regulated by concerning the process involves stages of investigation, prosecution, and trial in court. Criminal penalties for fisheries offenses are governed by the Fisheries Law, including imprisonment and maximum fines. Illegal fishing activities have serious implications for the fishing industry, including fish scarcity and the potential depletion of Indonesia's marine resources. Therefore, effective law enforcement is necessary to address these issues and ensure the sustainability of the fishing industry in Indonesia.Keywords: Resolution, Criminal Offense, Illegal Fishing.